Pelatihan Dasar Animasi 3D di SMK N 1 Sukasada - I Nyoman Saputra Wahyu Wijaya; I Ketut Purnamawan; I Made Putrama; Agus Aan Jiwa Permana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
SMK N 1 Sukasada is one of the Vocational High Schools in Singaraja. In the current pandemic, teachers and students have several problems. The decline in economic power for the majority of the community is one of the factors. Students must provide their tools and materials to participate in practical classes. Likewise, when teachers give online practicums. Economic problems will impact the inability to try practical activities. They are unable to provide tools and materials independently. Another problem, the attention of students to participate in learning activities. An effort is needed for teachers to increase students' interest in learning online. The creation of 3D assets is one of the basics to be able to use Augmented Reality technology. However, the teachers have not been prepared for training to create 3D assets. To solve this problem, community service activities are carried out for teachers in the form of basic 3D animation training